THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY IS MEDIATED BY SATISFACTION VARIABLES (STUDY OF CUSTOMER PERCEPTIONS ON BANK MANDIRI UNIT KUALA TANJUNG BRANCH BATUBARA DISTRICT, NORTH SUMATRA PROVINCE) - Ade Carlo Tiganna Damanik; Nazaruddin; Yeni Absah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Based on the research results, data analysis and discussion above, the following final conclusions can be drawn: There are differences between research conducted by previous researchers regarding the influence of service quality on consumer loyalty, where previous research stated that there is a significant influence on consumer loyalty. However, in this research, the service quality variable did not significantly influence customer/consumer loyalty. The user satisfaction variable has a positive and significant effect on the customer loyalty variable, where these results complement previous research which states that user satisfaction has a positive and significant effect on customer loyalty. Service quality and user satisfaction simultaneously influence customer loyalty with the results obtained namely 49.9% influencing loyalty and the remainder explained by other variables outside of the variables studied.